Mama's nightingale : a story of immigration and separation - Danticat, Edwidge, 1969- (Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, 2015)
When Saya's mother is sent to jail as an illegal immigrant, she sends her daughter a cassette tape with a song and a bedtime story, which inspires Saya to write a story of her own--one that just might bring her mother home.